Microglial pyroptosis: Therapeutic target in secondary brain injury following intracerebral hemorrhage - Gu, Lingui; Sun, Mingjiang; Li, Ruihao; Tao, Yihao; Luo, Xu; Zhang, Xingyu; Yuan, Ye; Xie, Zongyi (Frontiers in Cellular Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is a major cerebrovascular illness that causes substantial neurological sequelae and dysfunction caused by secondary brain injury (SBI), and there are no effective therapies to mitigate the disability. Microglia, the brain-resident macrophage, participates in the primary inflammatory response, and activation of microglia to an M1-like phenotype largely takes place in the acute phase following ICH. A growing body of research suggests that the pathophysiology of SBI after ICH is mediated by an inflammatory response mediated by microglial-pyroptotic inflammasomes, while inhibiting the activation of microglial pyroptosis could suppress the inflammatory cascade reaction, thus attenuating the brain injury after ICH. Pyroptosis is characterized by rapid plasma membrane disruption, followed by the release of cellular contents and pro-inflammatory mediators. In this review, we outline the molecular mechanism of microglial pyroptosis and summarize the up-to-date evidence of its involvement in the pathological process of ICH, and highlight microglial pyroptosis-targeted strategies that have the potential to cure intracerebral hemorrhage. This review contributes to a better understanding of the function of microglial pyroptosis in ICH and assesses it as a possible therapeutic target.